The hill we climb : an inaugural poem for the country - Gorman, Amanda, 1998- (Viking, 2021)
"On January 20, 2021, Amanda Gorman became the sixth and youngest poet to deliver a poetry reading at a presidential inauguration. Taking the stage after the 46th president of the United States, Joe Biden, Gorman captivated the nation and brought hope to viewers around the globe. Including an enduring foreword by Oprah Winfrey, this keepsake celebrates the promise of America and affirms the power of poetry"--